EXTH-47. PRECISION IMMUNOTHERAPY VACCINES FOR GLIOBLASTOMA USING CANCER IMMUNOGENOMICS AND SELECTIVE GENE ENRICHMENT STRATEGY - Trivedi, Vrunda (Neuro Oncol, 2020)
BACKGROUND: Development of successful immunotherapy targeting antigens in Glioblastoma (GBM) remains a challenge owing to the heterogeneous nature of GBM and the low mutation burden. It is therefore important to identify multiple tumor antigens that can be targeted simultaneously. Our goal is to develop a personalized RNA vaccination approach that employs the use of cancer immunogenomics in identifying tumor immunogenic epitopes and target enrichment strategies that allow for targeting only the tumor specific antigens. APPROACH: RNAseq and WES was performed for murine GBM tumors KR158 and GL261. Using our Open Reading Frame Antigen Network (O.R.A.N.) algorithm, we identified neoantigens and tumor-associated antigens (TAAs) which includes cancer testis and developmental antigens that are aberrantly over-expressed in the KR158 and GL261 tumors. The genes identified as harboring the target epitopes were subjected to a gene enrichment strategy which included hybridization, capture and amplification of our identified genes from a pool of total tumor cDNA. The precision RNA libraries generated from the enriched cDNA samples were then validated for enrichment of target genes using RNAseq. RESULTS: We predicted 12 neoantigens and 15 TAAs as immunogenic targets for the KR158 tumor and 192 neoantigens and 37 TAAs for GL261. Pre-capture and amplification, the 27 KR158 tumor genes constituted only 1.14% of the total tumor cDNA pool, however, we were able to enrich the selected genes to up to 95% of the cDNA pool. The IVT RNA library generated from the enriched cDNA templates also consisted of a 90–95% majority of the predicted tumor-specific genes and only 5–10% of the genes were background. CONCLUSION: We have demonstrated the ability to generate tumor antigen specific personalized RNA libraries for murine GBM tumors. RNA vaccines targeting specifically and simultaneously numerous tumor antigens, will pave way for the future of immunotherapy vaccines without the induction of intolerable autoimmunity.